2014
DOI: 10.1371/journal.pone.0115383
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Profiling in Cholangiocarcinoma: Prognostic and Therapeutic Implications

Abstract: BackgroundCholangiocarcinoma (CCA) is clinically heterogeneous; intra and extrahepatic CCA have diverse clinical presentations. Next generation sequencing (NGS) technology may identify the genetic differences between these entities and identify molecular subgroups for targeted therapeutics.MethodsWe describe successful NGS-based testing of 75 CCA patients along with the prognostic and therapeutic implications of findings. Mutation profiling was performed using either a) NGS panel of hotspot regions in 46 cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
419
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 398 publications
(442 citation statements)
references
References 43 publications
19
419
2
2
Order By: Relevance
“…Our results are in line with 3 additional case reports of dabrafenib and tramatenib in BRAF mutant ICC. These include 2 cases with a clinical benefit from MDACC (not detailed) and one case with a PR lasting more than 8.5 months from Penn University (11,12). While ideal, the conduct of future conclusive first-line phase III randomized clinical trials of dual BRAF/MEK inhibitors against gemcitabine plus cisplatin will be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with 3 additional case reports of dabrafenib and tramatenib in BRAF mutant ICC. These include 2 cases with a clinical benefit from MDACC (not detailed) and one case with a PR lasting more than 8.5 months from Penn University (11,12). While ideal, the conduct of future conclusive first-line phase III randomized clinical trials of dual BRAF/MEK inhibitors against gemcitabine plus cisplatin will be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have performed genetic analyses of BTC (15,16), and identified TP53 mutations in 8.2-35.7% of GBC cases (17,18), and KRAS mutations in 2-20% of GBC cases (18). KRAS mutations were identified in 20-67% of EBDC cases (19,20), and in 28.6-37.0% of AVC cases (21)(22)(23).…”
Section: Introductionmentioning
confidence: 98%
“…The results of these studies should be interpreted with caution as patients with metastatic disease have a worse survival compared to regional disease (2) as metastatic diseases may have a more aggressive biology (2,3,12). This is suggested by a genomic analysis study of cholangiocarcinoma in which it was shown EHC with mutations in BAP1 and PBRM1 are more likely to be associated with bone metastases and worse survival (13). This was also suggested in the ABC-02 trial where the benefit seen in metastatic disease (HR =0.74) was not as remarkable as in the unresectable locally advanced (HR =0.47) (4,14).…”
Section: Introductionmentioning
confidence: 99%